Return to Schooling for Public and Private Sector Higher Education Institutions of Khyber Pakhtunkhwa-Pakistan - Khan, Aamir; Khan, Himayatullah (International Journal of Economics and Financial Issues, 2020)
Human capital is a widely used concept in labor as well as in economics of education. The study examined return to schooling using data of 653 sample of higher education institutions of Khyber Pakhtunkhwa-Pakistan. The study also focused on estimating return to schooling with and without considering the endogeneity bias in schooling variable and compared the estimated return for public and private sector higher education institutions. Data was collected using well-designed questionnaire and the current study adopts Mincerian earning functions with its modified and extended forms using parental education as an instrument. The study found higher return to schooling for public sector respondents and reported considerable variation in estimated return after considering the endogeneity bias in schooling variable. Using an extended Mincerian earning function, the study found that higher return is associated with highest level of schooling and vice versa. Further investigation needed at micro and macro level along with critical evaluation of other instrumental variables for testing the endogeneity bias of schooling variable. Keywords: Modified Mincerian earning functions, Endogeneity bias, Instrumental variable, Return to Schooling, Parental education, Pakistan. JEL Classifications: I26, J24, C36 DOI: https://doi.org/10.32479/ijefi.10004